2020
DOI: 10.1177/0301006620929197
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Integration in the Processing of Chinese Characters as Revealed by Electroencephalography Frequency Tagging

Abstract: It is debated whether perceptual expertise of nonface objects, such as visual words, is indicated by holistic processing, which is regarded as a marker of perceptual expertise of faces. We address this question by frequency-tagged electroencephalography. Different parts of real or pseudo Chinese characters are presented at distinctive frequencies (6 or 7.2 Hz), which induce frequency-tagged steady-state visual-evoked potentials at occipital brain areas. The intermodulation response (e.g., 6 + 7.2 = 13.2 Hz) wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The frequency-tagged SSVEPs study revealed normal visual binding in adults with RD as in typical controls (Cai et al, 2020), suggesting intact visual holistic processing. We also found that Chinese characters elicited greater intermodulation response than pseudo characters in adults with RD, which is also consistent with typical controls.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The frequency-tagged SSVEPs study revealed normal visual binding in adults with RD as in typical controls (Cai et al, 2020), suggesting intact visual holistic processing. We also found that Chinese characters elicited greater intermodulation response than pseudo characters in adults with RD, which is also consistent with typical controls.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, signal-to-noise ratio (SNR) in SSVEP responses was used for further analysis. It was defined as the ratio of SSVEP response at a given frequency to its SSVEP responses at its nearby frequencies (Cai et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cai et al [ 12 ] used the IM-based steady-state visual-evoked potential (SSVEP) technique to study the integration of Chinese characters. In the experiment, participants needed to look at the real characters or fake characters with symmetrical structures flashing on the computer screen.…”
Section: Definitions Of Imsmentioning
confidence: 99%
“…Second-order IMs are considered low-order neural interactions [ 12 ]. As this experiment showed, second-order IMs may represent low-level bottom-up cognitive processing, in which participants passively perceived the flickering free from any expectations or focused attention.…”
Section: Definitions Of Imsmentioning
confidence: 99%